The effect of dietary omega-6 fatty acid enrichment in rodent models of military-relevant acute traumatic psychological stress and traumatic brain injury - Rusling, Matthew R.; DeMar, James C.; Chakraborty, Nabarun; Hoke, Allison V.; Miller, Stacy Ann; Rosenberger, John G.; Batuure, Andrew B.; Wilder, Donna M.; Sajja, Venkatasivasai Sujith; Long, Joseph B.; Hammamieh, Rasha; Gautam, Aarti (Frontiers in Microbiomes, 2024)
IntroductionSequelae from traumatic brain injuries (TBIs) and post-traumatic stress disorder (PTSD) are major career-limiting factors for combat soldiers. Overlap between TBI and PTSD symptoms alongside other common comorbidities complicate the diagnosis and treatment. Systems-level and high-throughput approaches are key in understanding the underlying biomolecular mechanisms and differentiating these conditions.MethodsThe present study identifies dietary factors and proposes mechanisms behind psychological stress and TBI, using established preclinical animal models and a multi-omics approach. Here, we used microbiome characterizations of rats exposed to simulations of blast-induced TBI and underwater trauma (UWT)-induced psychological stress. We further studied the effect of dietary omega-6 versus omega-3 polyunsaturated fatty acid (n-6, n-3 PUFA) enrichment on the insult responses. The use of excess n-6 PUFA was chosen due to its high prevalence in the Western diet and pro-inflammatory nature. Prior to TBI or UWT, animals were maintained for 6 weeks and continued thereafter on either a standard diet or two customized chows imbalanced and diminished in omega-3 content. Corresponding shams were carried out for all groups. Fecal bacterial microbiome populations were assessed using 16S rRNA gene sequencing.ResultsPhysiologic outcome modeling identified that dietary status affected post-TBI lactate dehydrogenase (LDH) and triglyceride levels, with n-3 PUFA having a large attenuating influence. The UWT model showed similar trends, with diet significantly altering LDH, terminal corticosterone (14 days post-exposure), and a fear behavior susceptibility. Fecal microbiome alpha diversity was significantly reduced by high levels of n-3 PUFA. Likewise, beta diversity of the microbiome was significantly affected by both diet and time but not exposure to TBI or UWT. Compositionally, temporal effects on the microbiome were more likely to be observed with the diets. The most affected features fell within the Proteobacteria phyla, in which n-3 PUFA enrichment significantly reduced Alphaproteobacteria in the TBI model and increased Gammaproteobacteria in the UWT group.DiscussionAll these observations can influence the vulnerability or resilience of the warfighter to blast-induced TBI and acute psychological stress. The microbiome mechanisms facilitate and provide a knowledge-driven unbiased panel of signatures to discriminate between the two insults and is an essential tool for designing precise care management.